Sharia Management Practices to Encourage Business Sustainability (Study on A Laying Hens Farm in Yogyakarta) - Anindya, Khoirina Noor; Putra, Muhammad Rozaan Eka; Sembodo, Khabib; Alviana, Septian Nurkholil (Universitas Muhammadiyah Magelang, 2025)
This research aims to explore sharia management practices in a business context to encourage business sustainability, especially in a laying hens farm in Yogyakarta. This research employs a qualitative approach and utilizes triangulation to ensure the reliability and validity of the data. The results indicate that sharia management not only discusses Islamic practices but also contributes to promoting business sustainability. The theoretical and practical implications of this research involve the development of business models oriented towards balancing economic profit, social responsibility, and, moreover, environmental sustainability.